The Study of Quality of Life in the Elderly With Hypertension Who are Member of Tehran Senile Culture House Clubs - Mahnaz Ahangari; Mohammad Kamali; Manouchehr Arjmand Hesabi (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: Today the rate of aged people in the world population is rapidly rising and some diseases and symptoms may affect on it .Hypertension (HT.) is prevalent in the elderly and has considerable impact on their quality of life. The objective of this study was to assess, the affect of the HT. on quality of life in the elderly in 2007. Methods & Materials: We conducted a cross-sectional and descriptive analytical study that included 300 subjects (191 subjects were healthy, 23 subjects with H.T. and others suffered from other diseases) who were >/=60 years of age and chosen randomly in Tehran Senile culture house club .We assessed quality of life, using the WHOQOL-BREF questionnaire with four domains: physical, psychological, social and environmental. Data gathering was done with face to face interviews method and the data were analyzed by using Correlation Coefficient Spearman and ANOVA in SPSS. Results: The result of study indicated that there is a significant difference between the mean of QOL scores in physical, psychological, environmental and overall domains of elderly with HT. and healthy persons (P<0.000) but there is not any difference in social domain. The quality of life scores between the groups, were strongly correlation with education (r=0.256, P<0.001), age (P<0.03), marital status (P<0.024) and gender (P<0.03) in physical domain. Conclusion: In this investigation patients with hypertension presented a poorer quality of life special in physical, psychological, environmental domains. This deterioration was not observed in social domain in the members of Tehran Senile Culture House Clubs, so prevention and in time control of this symptom possibly can improve their quality of life.